Stigma of mental health and attitude towards psychological help-seeking behaviour among students of a health science institute in Karnataka: a cross-sectional study - Naik, Poonam R; Shibu, Deepthi; Nagendra, Navya (Indian Journal of Community Health, 2024)
Background: Mental health illnesses are becoming a prime cause of concern among young adults. Many individuals with mental disorders do not get the necessary health care. Objectives: To assess the attitude towards seeking professional psychological help and stigma of mental illness among the students of a health science institute, to assess the association between stigma and attitude towards seeking psychological help with select socio demographic variables and to determine the correlation between attitude towards seeking professional psychological help and stigma of mental illness. Methods: A cross-sectional study was done on 215 students in Karnataka. The study tool consisted of questionnaires on socio-demographic profile and two sets of validated scales (Attitude Toward Seeking Professional Psychological Help Scale and Perceived Devaluation Discrimination Scale). Results: The study showed males had more positive attitude towards seeking professional psychological help than females. Individuals with history of present/past illness were more open towards seeking professional psychological help. Pearson correlation test between ATSPPHS and PDDS showed a negative correlation. Conclusions: Psychological help seeking attitude needs to be improved among the students. Educational institutes need to incorporate mental health awareness and stigma reduction program in their curriculum.